Razão instrumental e vontade : Max Horkheimer e o pessimismo metafísico de Arthur Schopenhauer - Macedo, André Motta (2016)
This dissertation investigates the relationship that Max Horkheimer sets, over his later writings, with the metaphysical pessimism of Arthur Schopenhauer. Thus, we analyze some texts that covering the 1940s, a time when Horkheimer embodies a radical critique of instrumental reason. This time preparing the transition to the final phase of his thought: the late phase that begins more or less in the years 1957/1959 and has its end in the year of his death in 1973. The mature Horkheimer is indeed a pessimistic declared, but only in relation to the theoretical alternatives that aim to safeguard the social welfare, ie, it is a purely theoretical pessimistic. In this sense, we try to determine what constitutes the concept of instrumental reason in the thought of Max Horkheimer, as well as some of its developments. Furthermore, we intentd to present some basic concepts of Schopenhauer thought, including the concept of Will, which relate to the philosophy of Horkheimer. And finally, we try to show the direct link made by Horkheimer, between instrumental reason and Will.